Parasitological and immunological aspects of trypanosoma (Nannomonas) congolense infections of the mouse (Musmusculus) and the tsetse fly (Glossina morsitans morsitans). - Nantulya, V.M. (University of Nairobi, 1978)
By determining the ID 50's of trypanosome populations In this thesis studies are described regarding the physiology of Trypanosoma congo1ense in the mouse and the vector. These studies have demonstrated that pleomorphism does occur in bloodstream T. congo1ense. At any point of parasitaemia in the mouse there were several morphological types of the parasite present, ranging from short to long forms. The various forms of T. congo1ense were identified according to Godfrey (1960). In the rising phase of parasitaemia the short forms predominated (over 70%), while at peak parasitaemia the parasites were highly pleomorphic, with large proportions of 'intermediate' (43%) and long forms (45%). Repeated SUb-passaging of such a pleomorphic trypanosome population at intervals of 3-4 days resulted in an increase in the proportion of the shorter forms and a decrease in the long and intermediate forms. Pleomorphism was observed both in normal and in lethally irradiated (900R) mice, even when the infection was initiated using a single organism. The various morphological types of T. congo1ense in clones prepared in irradiated mice were identical with respect to their surface variant antigen type as demonstrated by immunofluorescence. obtained from mice infected w ith a clone of T. congolense and by re-cloning it was shown that the short forms of this trypanosome species are more infective to a new mammalian host than the long forms. When newly emerged tsetse flies were fed on mice infected with cloned and uncloned derivatives of the three field isolates of T. congolense, high infection rates (22.4%) were achieved when such flies were fed on mice showing peak parasitaemia. The infection rates were low (7.1%) in flies fed on rising parasitaemia. These results indicate that the short form of T. congolense which predominates during the rising parasitaemia may have a lower capability to infect the vector than the long, and/or 'intermediate' forms which predominate at peak parasitaemia. The duration of the developmental cycle of T. congolense in the-tsetse fly varied from 7 to 40 days: in 45% of the infective flies the developmental cycle was completed within 12 days; and in 76%, within 18 days. The relationship between cyclical transmission and antigenic variation in T. congolense was investigated using cloned and uncloned derivatives of the three isolates. Antigenic analysis of freshly extruded metacyclics and their corresponding bloodstream forms was done by indirect ~mmunofluorescence and neutralization of infectivity tests using antisera prepared in mice by infection. It was found that mature metacyclics of a strain are antigenically identical. However, metacyclics of different strains carry different surface variable antigens. There was evidence to show that natural isolates of T. congolense may sometimes contain mixtures of different strains. Cyclical transmission of such isolates resulted in a simultaneous reversion of the various strains in these isolates to a mixture of corresponding metacyclic antigen types. The early bloodstream trypanosome populations obtained from fly-infected mice (normal or lethally irradiated) were not recognized by antisera to their corresponding metacyclics. These bloodstream trypanosome populations were antigenically heterogeneous, with certain antigen types predominating. Groups of mice were then exposed to various numbers of bites by tsetse flies infected with a clone of T. congolense. The mice were subsequently treated with Berenil when the initial infections became patent as were the uninfected control mice. The group of mice which received two doses of 12-15 infective fly bites on two occasions, separated by 3 weeks, were subsequently resistant to a further challenge by flies infected with the same clone of T. congolense. These mice were also immune to challenge by flies infected with antigenically different bloodstream derivatives of the same strain. The immunity, however, was not only strain-specific and